Bidirectional Regulation of AdpAch in Controlling the Expression of scnRI and scnRII in the Natamycin Biosynthesis of Streptomyces chattanoogensis L10 - Yu, Pin; Bu, Qing-Ting; Tang, Yi-Li; Mao, Xu-Ming; Li, Yong-Quan (Frontiers in Microbiology, 2018)
AdpA, an AraC/XylS family protein, had been proved as a key regulator for secondary metabolism and morphological differentiation in Streptomyces griseus. Here, we identify AdpAch, an ortholog of AdpA, as a “higher level” pleiotropic regulator of natamycin biosynthesis with bidirectional regulatory ability in Streptomyces chattanoogensis L10. DNase I footprinting revealed six AdpAch-binding sites in the scnRI–scnRII intergenic region. Further analysis using the xylE reporter gene fused to the scnRI–scnRII intergenic region of mutated binding sites demonstrated that the expression of scnRI and scnRII was under the control of AdpAch. AdpAch showed a bi-stable regulatory ability where it firstly binds to the Site C and Site D to activate the transcription of the two pathway-specific genes, scnRI and scnRII, and then binds to other sites where it acts as an inhibitor. When Site A and Site F were mutated in vivo, the production of natamycin was increased by 21% and 25%, respectively. These findings indicated an autoregulatory mechanism where AdpAch serves as a master switch with bidirectional regulation for natamycin biosynthesis.